Phosphorylation of the PKG substrate, vasodilator-stimulated phosphoprotein (VASP), in human cultured prostatic stromal cells - Cook, Anna; Haynes, J. (Elsevier Inc, 2007)
Nitric oxide (NO) is known to regulate contractility and proliferation of cells within the prostate, however, the mechanism by which this occurs is unknown. The cGMP-dependent protein kinase (PKG) signalling pathway may be involved, and recent work has shown that activation of this pathway can be assessed by analysis of phosphorylation of vasodilator-stimulated phosphoprotein (VASP). The aim of the current study is to characterise the expression of VASP in the human prostate and human cultured prostatic stromal cells (HCPSCs), and to investigate whether NO activates PKG in these cells. Our studies revealed that VASP is expressed, and that incubation of HCPSCs with PKG-activating cGMP-analogues or the NO-donor, SNP, caused a significant PKG-dependent increase in VASP serine-239 phosphorylation. In addition, SNP elicited a reduction in intracellular K+ in a time frame consistent with the phosphorylation of VASP and activation of PKG. These data demonstrate that VASP can be used to assess the NO/cGMP/PKG signalling pathway in HCPSCs. In addition, we demonstrate for the first time that SNP, probably via NO release, leads to phosphorylation of VASP in a manner consistent with PKG activation.